Probabilistic Choice and Congestion Pricing with Heterogeneous Travellers and Price-Sensitive Demand - Paul Koster; Erik T. Verhoef; Simon Shepherd; David Watling (Tinbergen Institute, 2014)
This paper deals with first-best and second-best congestion pricing of a stylised two-link network with probabilistic route choice of travellers. Travellers may have heterogeneous values of travel times and may differ in their idiosyncratic route preferences. We derive first-best and second-best tolls taking into account how the overall network demand responds to generalized costs including the tolls that are levied. We show that with homogeneous values of times the welfare losses of second-best pricing, of one link only, may be smaller if route choice is probabilistic. Furthermore, we show that with heterogeneous values of times, common second-best tolls and group-differentiated tolls can be very close when route choice is governed by random utility maximisation, leading to low welfare losses from the inability to differentiate tolls.
Keywords: R40; R41; R48; 330; Stochastic User Equilibrium; Second-best Congestion Pricing; Preference Heterogeneity; Scale Heterogeneity; Probabilistic Choice